Brain abscess complicating a diabetic man with Evans syndrome: a case report - Alam, Dilruba; Habib, Rumana; Muhtasim, Mahir; Haque, Md Rezwanul (BIRDEM Medical Journal, 2021)
Brain abscess is a relatively rare but potentially life threatening condition. The classic clinical triad of fever, headache and focal neurological sign may not be present in an immuno-compromised patient. The diagnostic delay may result in fatal outcome. A 52-year-old diabetic gentleman with history of chronic immunosuppressive therapy due to Evans syndrome presented with headache, generalized tonic- clonic seizure and right upper limb monoparesis. Clinical ground and neuroimaging was suggestive of pyogenic brain abscess. Patient was treated with antibiotic therapy for prolong period and there was complete clinical and radiological recovery. Birdem Med J 2021; 11(2): 137-141